Calycosin Inhibits the Malignant Behaviors of Lung Adenocarcinoma Cells by Regulating the circ_0001946/miR-21/GPD1L/HIF-1α Signaling Axis. (13th August 2022) - Zhou, Lixia; Chen, Wenxian; Yang, Hang; Liu, Jiaqin; Meng, Hui
Abstract : Objective . To clarify the potential function and molecular mechanism of calycosin in lung adenocarcinoma (LUAD) cells. Methods . LUAD cells (A549 and H1299) were treated with calycosin at different concentrations (25 nM, 50 nM, and 100 nM) for 24 h. The colony formation, invasion, and migration of the cells were assessed by colony formation, transwell, and scratch assays, respectively. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to determine the mRNA expression level of circ_0001946, miR-21, glycerol-3-phosphate dehydrogenase 1 like (GPD1L), and hypoxia-inducible factor-1 α (HIF-1 α ) in clinical tissue samples and LUAD cells. RNA pull-down assay and dual-luciferase reporter assay were performed to verify the relationship among circ_0001946, miR-21, GPD1L, and HIF-1 α . Western blot was performed to detect the protein expression of epithelial-mesenchymal transition (EMT) process-related genes (E-cadherin, N-cadherin, and snail) and GPD1L as well as HIF-1 α . Results . Calycosin inhibited colony formation, invasion, migration, and EMT progression in A549 and H1299 cells. Besides, calycosin was able to regulate the expression of circ_0001946, miR-21, GPD1L, and HIF-1 α in LUAD cells. According to the findings of QRT-PCR, the expression level of circ_0001946 and GPD1L in LUAD tissues was significantly lower than that in adjacent noncancerous normal tissues, and the expression of miR-21 and HIF-1 α was also significantly increased in clinical tissue samples. In addition, there was a targeted regulatory relationship among the above four expressions. Knockdown of circ_0001946 expression in A549 cells treated with calycosin enhanced the malignant behavior of A549 cells and inhibited the anticancer effect of calycosin. However, the knockdown of miR-21 promoted the anticancer effect of calycosin and inhibited the malignant behavior of A549. Conclusion . Calycosin can inhibit colony formation, invasion, migration, and EMT process of LUAD cells via regulating the circ_0001946/miR-21/GPD1L/HIF-1 α signaling axis and could be a promising therapeutic drug for LUAD.